An extension of Aaker's brand personality model from Islamic perspective: a conceptual study. (14th September 2015) - Ahmed, Muhammad; Jan, Muhammad Tahir
Abstract : Purpose: – The purpose of this paper is to browse literature based on Aaker's brand personality modal and highlight criticism on it. Furthermore, the study proposes an Islamic brand personality modal based on Islamic teachings. Design/methodology/approach: – Extensive research on Muslim characteristics based on Qur'an, hadith and scholarly work of traditional and modern scholars has been used to assess Aaker's model. Expert opinions of faculty members from relevant field are also taken into consideration to propose Islamic brand personality model. Findings: – Aaker's brand personality dimensions have been revised in the light of Islamic teachings. As a result, few pre-existing dimensions have been re-named and several new dimensions such as moral character and trustworthiness are also included. Research limitations/implications: – Considering the gap found in literature, the need to conduct brand personality research in the service industry such as Islamic banks is highlighted. Practical implications: – Islamic brand personality model may help marketers effectively differentiate Islamic brands such as Islamic banks. It may also reinforce advertising techniques/tools to attract a large Muslim consumer market. Originality/value: – This paper is one of the early attempts to see brand personality from Islamic perspective.